The Affecting of Regional Original Revenue, General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund on Capital Expenditures in Central Java - Prabowo, Sigit; Bawono, Icuk Rangga (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2023)
The goal of this research is to figure out how region original revenue, general fund allocation, specific fund allocation, and the Revenue Sharing Fund affect capital spending Methods of saturation sampling, the population in this study was comprised of twenty-nine regencies and six cities in Central Java from 2016 to 2018. The data used in this study is secondary data gathered from the budget realization report of the Financial Supervisory Agency of Central Java Province. Multiple linear regression analysis is used in the analytical procedure. The Capital Expenditure is influenced by General Fund Allocation, Specific Fund Allocation, and Revenue-sharing Fund, although Region Original Revenue has no impact on the capital expenditure.